The Myth of Disenchantment: Magic, Modernity, and the Birth of the Human Sciences by Jason A. Josephson-Storm - Fernandes, Dmitri Cerboncini; Moreira-Almeida, Alexander (Journal of Scientific Exploration, 2021)
We live in a contradictory world. Self-proclaimed “skeptics”, as the original meaning itself suggests, should first of all strive for proper scientific rationality, for reflective and objective distancing in the apprehension of reality, for methodological caution and for the extended ability to theoretical and philosophical understanding of intricate problems, in practice, too often have entrenched themselves in dogmatic groups. Inquisitors often endowed with the appearance of religious fanaticism, in the worst sense of the term, invest their energies in a crusade of attacks to everyone to whom they attribute mistakes, naivety or even bad intentions. In practice, the universe of those who do not fit in their often restricted, idealized and naïve views of scientific practice. With them, there is hardly any possibility of frank dialogue or opening to research fields that escape their conceptions of what science and philosophy can approach and how they should operate. Charlatans, backward, believers, superstitious; these are some disqualifications generally granted to researchers who dare to go beyond the limits they established for science and rationality. To substantiate their certainties, such self-proclaimed skeptics often claim to base their approach to science on the examples given by highly regarded scientists and philosophers of the past. We speak here of scholars of the stature of Giordano Bruno, Francis Bacon, René Descartes, Isaac Newton, the Encyclopedists, Immanuel Kant, Arthur Schopenhauer, Sigmund Freud, James Frazer, the Vienna Circle, Max Weber, etc. Despite their different approaches, we are talking about many of the very founders of modern Western knowledge. The self-proclaimed contemporary “skeptics” claim their inscriptions in the tradition inaugurated by these illustrious intellectual ancestors. They claim to defend with determination such a rationalist tradition against “pseudoscientists” and “mystic-religious" philosophers who, according to their opinions, wish to corrupt it through insidious insertions in a field that would not rightfully belong to them. This would be their main mission.